Effect of micronutrient supplements on influenza and other respiratory tract infections among adults: a systematic review and meta-analysis - Wafaie Fawzi; Sabri Bromage; Ajibola Ibraheem Abioye (BMJ Global Health)
Acute respiratory tract infections (ARIs) are a leading cause of ill-health and death globally. Individual or multiple micronutrients have been shown to modulate immune function and affect the risk and severity of a number of infectious diseases. We systematically reviewed the evidence on the impact of micronutrient supplements to reduce the occurrence of ARIs and shorten the duration of ARI symptoms among adults. Random effects meta-analyses were conducted to estimate the pooled effects of vitamin D, vitamin C, zinc and multiple micronutrient supplementation (MMS) on the occurrence of ARIs and the duration of ARI symptoms. Vitamin D supplementation reduced the risk of ARI (risk ratio (RR)=0.97; 95% CI 0.94 to 1.00; p=0.028) and shortened the duration of symptoms (per cent difference: −6% (95% CI −9% to −2%; p=0.003)). The RR of vitamin D to prevent ARI was farther from the null when diagnosis was based on clinical diagnosis or laboratory testing, compared with self-report and when the loading dose was <60 000 IU. Vitamin C supplementation reduced the risk of ARIs (RR=0.96; 95% CI 0.93 to 0.99; p=0.01) and shortened the duration of symptoms (per cent difference: −9% (95% CI −16% to −2%; p=0.014)). The effect of vitamin C on preventing ARI was stronger among men and in middle-income countries, compared with women and high-income countries, respectively. Zinc supplementation did not reduce the risk of ARIs but shortened the duration of symptoms substantially (per cent difference: −47% (95% CI −73% to −21%; p=0.0004)). Our synthesis of global evidence from randomised controlled trials indicates that micronutrient supplements including zinc, vitamins C and D, and multiple micronutrient supplements may be modestly effective in preventing ARIs and improving their clinical course. Further research is warranted to better understand the effectiveness that individual or multiple micronutrients have on SARS-CoV-2 infection and treatment outcomes.